Urushi Art Japan. - Shiraishi, Kazumi (Tokyo : Arisumi Mitamura, 1997)
Jitoku, Akatsuka ; Jiho, Mitamura ; Hideo, Mitamura ; Arisumi, Mitamura
National Museum of Modern Art, Tokyo, June 1997
Tekst ook in Japans.
kunstcatalogus
Keywords: Japan